RETRACTED: Role of Renewable Energy Consumption and Technological Innovation to Achieve Carbon Neutrality in Spain: Fresh Insights From Wavelet Coherence and Spectral Causality Approaches - Zhao, Yawen; Ramzan, Muhammad; Adebayo, Tomiwa Sunday; Oladipupo, Seun Damola; Adeshola, Ibrahim; Agyekum, Ephraim Bonah (Frontiers in Environmental Science, 2021)
This research offers a new perceptive of the dynamic connection between CO2 and globalization, technological innovation, economic growth, and renewable energy consumption in Spain. The current research applied the wavelet tools to assess these interconnection utilizing data stretching from 1980 to 2018. The outcomes of these analyses disclose that the association amongst the series evolves over frequency and time. The current analysis uncovers notable wavelet coherence and strong lead and lag connections in the frequency domain, while the time domain indicates inconsistent correlations amongst the variables of interest. The outcomes of the wavelet analysis from economic perspective affirms that in the short and medium-term, globalization, GDP and technological innovation contribute to environmental degradation; though in the long-term globalization, economic growth and technological innovation does not contribute to degradation of the environment. Moreover, at different frequencies, renewable energy consumption helps to mitigates environmental degradation in Spain. Furthermore, the spectral causality test unveiled that in the long-term, renewable energy utilization, globalization, technological innovation and economic growth can predict CO2 emissions in Spain